2013
DOI: 10.1007/s00401-013-1079-8
|View full text |Cite
|
Sign up to set email alerts
|

GDNF mediates glioblastoma-induced microglia attraction but not astrogliosis

Abstract: High-grade gliomas are the most common primary brain tumors. Their malignancy is promoted by the complex crosstalk between different cell types in the central nervous system. Microglia/brain macrophages infiltrate high-grade gliomas and contribute to their progression. To identify factors that mediate the attraction of microglia/macrophages to malignant brain tumors, we established a glioma cell encapsulation model that was applied in vivo. Mouse GL261 glioma cell line and human high-grade glioma cells were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 37 publications
1
67
0
1
Order By: Relevance
“…Subsequent research revealed that GDNF strongly induces glioma cell proliferation and migration [11-13]. Knocking down expression of GDNF or its receptor GDNF family receptor α1 (GFRα1) effectively inhibits the pathological progression of glioma [14, 15]. GDNF mainly exerts its functions via the GFRα1/Ret receptor complex [16].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research revealed that GDNF strongly induces glioma cell proliferation and migration [11-13]. Knocking down expression of GDNF or its receptor GDNF family receptor α1 (GFRα1) effectively inhibits the pathological progression of glioma [14, 15]. GDNF mainly exerts its functions via the GFRα1/Ret receptor complex [16].…”
Section: Introductionmentioning
confidence: 99%
“…2a). In some in vivo studies, microglia were polarized and recruited by tumor-released chemokines such as colony-stimulating factor, monocyte chemotactic protein-1, hepatocyte growth factor, and glial cell line-derived neurotrophic factor [32,33] and migrated to the tumor cells. The activated microglia released active substances such as granulocyte macrophage colony-stimulating factor that further increased glioma migration [10].…”
Section: Discussionmentioning
confidence: 99%
“…[82] On the other hand, the expression and activity of GDNF and its receptor GFRα1 are increased by their soluble forms in gliomas. [130][131][132][133] Based on the above, we developed a lentiviral vector in which the expression of tGAS1 is inducible. [87,88] This soluble form of GAS1 acts both in autocrine and paracrine manners in GBM cells and inhibits glioma tumor growth in vivo.…”
Section: Potential Therapeutic Effect Of Gas1 For the Treatment Of Glmentioning
confidence: 99%